(untitled) (Web of Teachers: Inderscience Research, 2024)
The article discusses the organization of independent work as a way of active, purposeful acquisition of new knowledge and skills by a student in the process of frontal, group and individual educational activities, carried out under the guidance of a teacher, but without the direct participation of a teacher.